Dylematy ustalania wartości godziwej - Hasik, Wojciech (Dilemmas of Establishing Fair Value, 2007)
An extensive usage of fair value is one of many consequences of Polish accounting law harmonization with Pan-European accounting regulations (IFRS) and direct IFRSs' implementation into Polish legal system (effects of Regulation no 1606/2002 of European Parliament and Council) in scope of consolidated financial statements preparation. The purpose of this paper is to identify the problems resulting from necessity of using fair value as a base for assets and liabilities valuation. Many of problems indicated in the paper is of very complex nature. This is because we can find their sources in the very conceptual, as well as historical background of fair value concept. Other have mostly technical character, therefore the practice itself should come up with relevant solutions (good practices) which could be recognized as the generally accepted principles in this scope. Performing analysis of sources and background of the indicated problems the author formulates number of questions which remain unanswered. The author hopes they will initiate the further public discussion within scope of fair value, which could result in giving the expected answers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 48-52